Thermal simulation and validation of LED-based luminaires using two-resistor compact thermal model. (October 2014) - Yurtseven, MB; Onaygil, S; Ogus, G
The increase in the LED junction temperature is an important problem since it directly affects the lumen output and the colour characteristics of the LED chips, resulting in low performance in LED-based lighting systems. In this study, commercial computational fluid dynamics software is used with the JEDEC's two-resistor compact thermal model to analyse the temperature distribution in two selected luminaires. It is aimed to show that use of the two-resistor model and measurement combination is a fast and easy way of predicting thermal behaviour of the system and LED junction temperatures instead of trial and error designs and thus ensures a better estimation for the total luminous flux of the luminaire and lowers the costs and time required for the prototyping processes.